Supporting Collaborative and Creative Mathematical Thinking Through a Multimodal Digital Textbook: Design and Evaluation of a Wordwall-Integrated Learning Environment - Arie Anang Setyo; Ania Yulita Sipahelut; Irna Rusani (Universitas Papua, 2026)
Traditional mathematics instruction has often been insufficient in fostering essential twenty-first-century competencies, particularly students’ collaborative and creative thinking skills. Addressing this challenge, this study aimed to develop and evaluate a Wordwall-integrated multimodal digital mathematics textbook designed to enhance these competencies among elementary school students. The development process was guided by the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design framework. Following expert validation, the textbook was implemented using a one-group pretest–posttest design involving 20 fourth-grade students. Data were collected through expert validation instruments, practicality questionnaires, collaboration observation rubrics, and a standardized creative thinking assessment. The validation results demonstrated a high level of feasibility across media (95%), content (90%), and instructional design (92%) dimensions. Practicality evaluations further indicated highly positive responses from teachers and students, with an overall mean score of 95.5%. Effectiveness analysis revealed notable improvements in students’ learning outcomes and twenty-first-century competencies, with collaboration skills reaching a high category (70.0%) and creative thinking skills showing moderate improvement (N-gain = 0.60). Furthermore, posttest scores were significantly higher than pretest scores (p < .001), indicating meaningful learning gains following the intervention. These findings suggest that Wordwall-integrated multimodal digital textbooks can serve as an effective instructional resource for promoting collaborative and creative thinking skills in elementary mathematics education and provide empirical support for the integration of multimodal and gamified learning environments in mathematics classrooms.